La célébration du Mawlid dans l’Occident musulman médiéval à la lumière des fatwā-s mālikites compilées par al-Wansharīsī - Ahmed Oulddali (Revue des Mondes Musulmans et de la Méditerranée)
The celebration of the Prophet’s birthday was instituted in the Muslim West during the 7th/13th century. But from the beginning it sparked a lively debate in Mālikite circles where it was first considered as a blameworthy religious innovation (bidʿa), before being accepted under certain conditions which are specified in the legal literature. This article discusses the attitude of the Mālikī scholars from North Africa and al-Andalus towards the Mawlid. It is based on a series of legal consultations (fatwā-s) mentioned in the Miʿyār of al-Wansharīsī (d. 914/1508). We analyze the various points of view expressed by jurists and the reasons given to justify them. The study is also interested in the evolution of the Mālikite position on the Mawlid and on the way in which this non-canonical festival was celebrated among some followers of Sufism.